Jurong Island groundwater study : hydrological and hydraulic investigations - Wong, Shao Jie. (2013)
Groundwater which is found in Jurong Island would become a new water resource for future Singapore. A pilot test study was carried out on Jurong Island mainly in reclaimed area from August to October 2010. Researches which were done with some assumptions made in previous studies aimed to understand the characteristics and behaviours of each parameter under different kind of situations.